Penerapan Isometric Handgrip Exercise untuk Menurunkan Tekanan Darah pada Penderita Hipertensi di Wilayah Puskesmas Pucangsawit - Mita Rahayu; Hermawati Hermawati (Asosiasi Riset Ilmu Kesehatan Indonesia, 2024)
Background: Hypertension that occurs in the world of the entire world population is 22% (WHO, 2021). Based on data obtained from the Pucangsawit Community Health Center, in 2023 there were 1,623 cases of Primary Hypertension. Isometric handgrip exercise therapy is a non-pharmacological therapy to help lower blood pressure. Objective: determine changes in blood pressure values in two respondents with hypertension before and after being given isometric handgrip therapy. Method: This research is a case study research using descriptive methods, namely by observing and interviewing two respondents with hypertension who are at risk of developing kidney disease and other diseases with a decrease in blood pressure results that become normal. Results: There was a decrease in blood pressure values in Mrs. S from 143/90 mmHg to 135/85 mmHg, while in Mr. N decreased from 160/98 to 150/90 mmHg. Conclusion: after applying isometric handgrip therapy to Mrs. S and Mr. N there is a decrease in blood pressure values ​​in hypertensive sufferers. This shows that the isometric handgrip can reduce blood pressure to normal.